A breath of fresh air for atmospheric CO2 utilisation: a plasmon-assisted preparation of cyclic carbonate at ambient conditions. Issue 13 (9th March 2021) - Guselnikova, Olga; Postnikov, Pavel; Kosina, Jiri; Kolska, Zdenla; Trelin, Andrii; Svorcik, Vaclav; Lyutakov, Oleksiy
Abstract : We proposed a hybrid plasmonic catalyst for atmospheric CO2 transformation to carbonates under the ambient conditions of atmospheric pressure and room temperature. Abstract : The increase of CO2 levels is becoming a global problem in the 21 st century, leading to current requests for new advanced materials and methods of CO2 utilisation. Here, we propose a hybrid plasmonic catalyst for the transformation of CO2 to carbonates in quantitative yields under ambient conditions, in contrast to the commonly applied elevated temperature and pressure. The proposed catalyst presents a combination of gold nanoparticles modified by triazabicyclodec-5-ene (TBD). TBD is responsible for CO2 fixation, forming a zwitterionic adduct near the plasmonic surface. The terminating stage, namely the interaction of the zwitterionic adduct with the epoxide, is pumped by plasmonic triggering and is the first example of plasmon-assisted CO2 cycloaddition. Taking advantage of the proposed catalyst, we achieved an unprecedented turnover number, turnover frequency, and apparent quantum yield, even in the case of air as a CO2 source and light as an energy input. Control experiments, including variation of illumination conditions and temperature, prove that the photochemical pathway proceeds through plasmon excitation.